Relationship Marketing Dalam Perspektif Islam - Fageh, Achmad; Fatmariyah, Fatimatul; AS, Fathor (Institut Agama Islam Negeri Madura, 2022)
From an Islamic perspective, the concept of relationship marketing is standard and internationally recognized. However, so far, there is no such thing. Indeed, in Islamic teachings, the idea of RM brought by western scientists has been contained in the Al-Qur'an and Al-Hadits. Even the concept of relationships in Islamic education is more comprehensive. This article aims to explain the idea of relationship marketing from an Islamic perspective and its main components. This type of research is qualitative through literature study and content analysis. The analysis results show that the concept of relationship marketing from an Islamic perspective is demonstrated through various terms, components, and constructs, including Islamic relationship marketing, shariah relationship marketing, Islamic customer relationship marketing, shariah customer relationship marketing, etc. Islamic Relationship Marketing (IRM) was developed from relationship marketing and Islamic ethical behavior. Shariah Relationship Marketing (SRM) was designed from relationship marketing and Shariah Compliance. The components of IRM are Islamic ethical behavior, social bonds, structural bonds, and financial bonds, and the features of SRM are bonding, communication, commitment, complaint handling, trust, and sharia compliance.